Analyse des verbes locatifs abandonner, laisser et quitter suivant les restrictions sémantico-syntaxiques de leur entourage en français dans une perspective historique et contrastive - Żłobińska-Nowak, Aleksandra (Neophilologica, 2017)
The aim of this paper is to examine the three French locative verbs abandonner, laisser and quitter qualified as synonymous by most French dictionaries. All these verbs can describe the same semantic invariant which is the concept of rupture and separation and generate polysemic extension to the semantics of movement. The most common uses of abandonner and quitter are based on the same syntactic construction [SN figure V SN ground] which, in this form, does not explain any restrictions. In the following study the Author will present a detailed analysis of the characteristics of these three verbs from a diachronic perspective which, perhaps, will enable a better understanding of their functioning in language, thus making their use by non-native speakers more suited to extralinguistic circumstances.